Design and development of an automatic feeder for Penaeus vannamei culture - Nila Rekha, P.; Ambasankar, K.; Stanline, S.; Sethuraman, K.; Syamadayal, J.; Panigrahi, A.; guruvasagam, Kumara (Indian Journal of Fisheries, 2018)
The introduction of Penaeus vannamei Boone, 1931, during 2009 opened up a new vista in Indian aquaculture. Presently, 90% of shrimp farming in the country is contributed by P. vannamei. The potential productivity level is around 10-12 t ha-1 and handling the feed during the course of culture increases considerably especially towards the end of culture period. This calls for automation in shrimp farming especially for feeding practices so that labour problem faced by the industry could be solved. The biosecurity requirement for vannamei farming can also be best met with the use of automatic feeders. The present study attempted designing and development of an indigenous automatic feeder for P. vannamei culture. The feeder design comprised four major components viz., feed hopper, distribution mechanism, a control unit for regulating the quantity and frequency of feeding and the power supply unit. Automation is effected through two timers with a digital display so that dispensing of the feed as well as duration of feeding could be easily adjusted by the farmers. Performance evaluation of the automatic feeder was done exhaustively and the results clearly showed that the maximum dispersion distance was 39 m dia and the maximum quantity of feed dispersed was 620 g in 5 sec. On farm evaluation of the feeder was also carried out in a shrimp pond and the installation height was optimised as approximately 75 cm - 1 m from the water level for facilitating better dispersion of the feed.